2000
DOI: 10.1046/j.1365-8711.2000.03261.x
|View full text |Cite
|
Sign up to set email alerts
|

On the least action principle in cosmology

Abstract: Given the present distribution of mass tracing objects in an expanding universe, we develop and test a fast method for recovering their past orbits using the least action principle. In this method, termed FAM for fast action minimization, the orbits are expanded in a set of orthogonal time basis functions satisfying the appropriate boundary conditions at the initial and final times. The conjugate gradient method is applied to locate the extremum of the action in the space of the expansion coefficients of the o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 41 publications
3
69
0
Order By: Relevance
“…The reason for this is the strict criteria we have applied in selecting the "LG observer" in the mock catalogs, aimed at matching the quietness and moderate density environment of the observed LG. Removing these selection criteria boosts the error to > ∼ 300km s −1 , consistent with previous studies (Nusser & Branchini 2000). Nonlinear dynamical reconstruction methods can potentially reduce LG actors + four external groups.…”
Section: Cosmological Constraints On 20-100 Mpc Scalessupporting
confidence: 87%
“…The reason for this is the strict criteria we have applied in selecting the "LG observer" in the mock catalogs, aimed at matching the quietness and moderate density environment of the observed LG. Removing these selection criteria boosts the error to > ∼ 300km s −1 , consistent with previous studies (Nusser & Branchini 2000). Nonlinear dynamical reconstruction methods can potentially reduce LG actors + four external groups.…”
Section: Cosmological Constraints On 20-100 Mpc Scalessupporting
confidence: 87%
“…The bias produces an undesired smoothing of density field along the radial direction. The smoothing width (in km s −1 ) is equal to the rms random error in the velocities ∼200–300 km s −1 (Branchini, Eldar & Nusser 2002; Nusser & Branchini 2000). Therefore, the bias is more pronounced in non‐linear methods which aim at probing small scales.…”
Section: Discussionmentioning
confidence: 99%
“…This point remains to be further studied and quantified. The linear component can be accurately traced back in time on large scales ≳5 h −1 Mpc from Eulerian to Lagrangian coordinates yielding fields that are more correlated with the initial conditions than the Eulerian representation. This implies that Eulerian grid‐based methods (as opposed to particle‐based methods; see Peebles ; Nusser & Branchini ; Branchini, Eldar & Nusser ; Eisenstein et al ; Lavaux et al ) could be used to recover BAO or other physical signals. We have demonstrated that one can compute the non‐linear component from the linear component with LPT.…”
Section: Discussionmentioning
confidence: 99%